The challenge of training for strength and endurance - Gross, M. (Science and Skiing VII, 2018)
When training plans combine both endurance and strength sessions, this is referred to as concurrent training. Alpine skiing is a prime example of a sport in which high strength and muscle power demands coincide with considerable reliance on the aerobic energy system, but this is also the case for a number of other sports. Given the fact that strength training and endurance training are by nature divergent, setting different stimuli that might lead to conflicting adaptations poses challenges for coaches and athletes in sports in which concurrent training is nonetheless essential.